Eleições, partidos e política orçamentária no Brasil: explorando os efeitos das eleições locais na política nacional - Barone, Leonardo Sangali (2014)
This research aims to investigate party linkages between brazilian local and national/state level politicians and it's effects on elections, party politics and legislative behavior. The mains goal is to test if mayoral partisanship affects party's candidates performance, budgetary decisions in the National Congress and party's ability to gather local financial and political support. I use a regression discontinuity design to estimative the effects of local vitory on the dependent variables. I include data on brazilian politics from 1996 to 2012